The Category of Neighbourhood in Islamic Modernism of Yugoslavia. "Fetve" of Husein Đozo - Olimpia Dragouni (Colloquia Humanistica, 2015)
The Category of Neighbourhood in Islamic Modernism of Yugoslavia. "Fetve" of Husein Đozo